1990
DOI: 10.1093/carcin/11.11.2001
|View full text |Cite
|
Sign up to set email alerts
|

Complexes involving quercetin, DNA and Cu(II)

Abstract: The genotoxic flavonoid, quercetin, was shown to bind to both double-stranded and single-stranded DNA with concomitant changes in absorption spectrum and fluorescence emission spectrum of quercetin. Quercetin and Cu(II) were shown to form a charge transfer complex that decayed in oxygen-dependent reaction(s) and this decay was accelerated by DNA. Analysis of the three component system, DNA--querectin--Cu(II), led to a discussion of the complexes likely to be involved in the initial reactions that lead, ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
47
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 0 publications
10
47
0
1
Order By: Relevance
“…Similar pro-oxidant effects have been reported for other antioxidant phytochemicals including flavonoids, [33] tannins [34] and curcumin. [35] Previous studies have shown that transition metal ions, such as copper or iron, can enhance the conversion of the anti-oxidant to the pro-oxidant state.…”
Section: Other Phenolic Aloe Vera Constituentssupporting
confidence: 80%
“…Similar pro-oxidant effects have been reported for other antioxidant phytochemicals including flavonoids, [33] tannins [34] and curcumin. [35] Previous studies have shown that transition metal ions, such as copper or iron, can enhance the conversion of the anti-oxidant to the pro-oxidant state.…”
Section: Other Phenolic Aloe Vera Constituentssupporting
confidence: 80%
“…Thus, although many plant species have very high antioxidant contents, it is possible that the individual components may act as either antioxidants or as pro-oxidants and thus may also be effective in the treatment of cancer, as well as in its prevention at different concentrations. Similar pro-oxidant effects have been reported for other antioxidant phytochemicals including flavonoids 11 and tannins. 12 Furthermore, the presence of transition metal ions such as copper or iron in an extract can further enhance the conversion of the antioxidant to the prooxidant state.…”
Section: Introductionsupporting
confidence: 81%
“…Thus, although many plant species have very high antioxidant contents, it is possible that the individual components may act as either antioxidants or as oxidants and thus may also be effective in the treatment of cancer, as well as in its prevention at different concentrations. Similar pro-oxidant effects have been reported for other antioxidant phytochemicals including flavonoids 10 and tannins. 11 The pro-oxidant/antioxidant effect of plant extracts is due to a balance between the free radical scavenging activities and reducing power of their phytochemical components.…”
Section: Introductionsupporting
confidence: 81%